Mizan and Village Waste Management: A Qur’anic Ecotheological Study of Surah Al-Raḥmān 55:7–9 in Kertajaya Village - Wildan, Wildan; Heriyanto, Heriyanto; Nurdin, Yanyan (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2026)
This study examines mīzān, meaning balance, measure, justice, and equilibrium, in Surah al-Raḥmān 55:7–9 and explores its relevance to waste-management conditions in Kertajaya Village, Pebayuran Subdistrict, Bekasi Regency. The study employed a qualitative design combining library research and field research through an ecotheological approach. Textual analysis examined the interpretations of Ibn Kathir, al-Sa‘di, Hamka, and M. Quraish Shihab, while field data were collected through semi-structured interviews with eight key informants and observations of irrigation channels, residential drainage, and riverbank areas. The textual data were analyzed comparatively, and field data were analyzed using the Miles and Huberman interactive model. The findings show that the four exegetes associate mīzān with justice, proportion, equilibrium, restraint, and the divinely established order of creation. Drawing on these themes, the study develops ecological carrying capacity, environmental justice, and ecological piety as analytical syntheses for interpreting local environmental conditions. Field findings indicate visible pressure on irrigation channels and residential drainage through waste accumulation, water-hyacinth growth, limited disposal facilities, inconsistent maintenance, and uneven participation in collective cleaning activities. Household practices, including waste burning, burial, and disposal near waterways, were shaped by constrained disposal options and the absence of a consistent village-level waste-management system. The study concludes that environmental problems in Kertajaya Village arise through the interaction of household practices, limited environmental services, weak maintenance arrangements, and insufficient local coordination. Qur’anic ecological ethics can support environmental responsibility when connected with practical institutions, accessible waste services, environmental education, and community participation. The proposed Village Ecotheology Forum is presented as an initial community-based option that requires further testing through participatory research.